2012
DOI: 10.1089/jmf.2011.1996
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofEcklonia cavaPolyphenol in Individuals with Hypercholesterolemia: A Pilot Study

Abstract: We evaluated the efficacy and safety of Ecklonia cava polyphenol (Seapolynol™, a polyphenol antioxidant and anti-inflammatory agent purified from E. cava) during a 12-week treatment period (400 mg orally once daily) in individuals with hypercholesterolemia and performed subgroup analysis for metabolic syndrome (MetS). As a noncomparative study, forty-six individuals (M:F=22:24, mean age=54±11 years) with fasting total cholesterol concentration >240 mg/dL or low-density lipoprotein cholesterol (LDL-C) concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 28 publications
(23 reference statements)
1
22
0
1
Order By: Relevance
“…In Korean adults with increased cholesterol, however, a significant reduction in total cholesterol, LDL-C, and C-reactive protein was observed compared with baseline values following treatment with Ecklonia cava polyphenol extract at a dosage of 400 mg/d for 12 weeks 156 . Potential mechanisms of action may be associated with the inhibition of adipogenesis, as the phlorotannin dieckol has been shown to downregulate AMP-activated protein kinase (AMPK) signaling in 3T3-L1 preadipocytes 157 …”
Section: Nutritional Composition Of Edible Seaweedsmentioning
confidence: 99%
“…In Korean adults with increased cholesterol, however, a significant reduction in total cholesterol, LDL-C, and C-reactive protein was observed compared with baseline values following treatment with Ecklonia cava polyphenol extract at a dosage of 400 mg/d for 12 weeks 156 . Potential mechanisms of action may be associated with the inhibition of adipogenesis, as the phlorotannin dieckol has been shown to downregulate AMP-activated protein kinase (AMPK) signaling in 3T3-L1 preadipocytes 157 …”
Section: Nutritional Composition Of Edible Seaweedsmentioning
confidence: 99%
“…E. cava is currently being explored for its health-promoting properties due to its high phlorotannin contents (~18% on a dry weight basis). It is known to contain numerous phlorotannins, which includes dieckol, PFFA, PHB, PPB, phlorofucofuroeckol, 6,6′-bieckol, 8,8′-bieckol, 2- O -(2,4,6-trihydroxyphenyl)-6,6′-bieckol, eckstolonol, 2-phloroeckol, 1-(3′,5′-dihydroxyphenoxy)-7-(2″,4″,6-trihydroxyphenoxy)-2,4,9-trihydroxydibenzo-1,4-dioxin, eckol, 7-phloroeckol, phlorotannin A, and phloroglucinol [23,24,25,26,27,28]. The phlorotannins have a resilient dibenzo-1,4-obesityxin backbone, which presumably aids molecular interactions with various biomolecules [29,30].…”
Section: Resultsmentioning
confidence: 99%
“…Tylophorine compounds could be novel leads for further drug development on their own or as templates for drug design (Islam et al 2020 ). Tylophorine and related alkaloids, isolated from Tylophora indica Merr., inhibit TGEV replication for anti-coronavirus activity and suppress nitric oxide production in RAW264.7 cells, a measure of antiinflammation (Lee et al, 2012a , b ). Additionally, a pharmacokinetic study demonstrated high and comparable oral bioavailabilities of tylophorine (65.7%) in rats (Lee et al, 2012a , b ).…”
Section: General Inhibitors Of Replicationmentioning
confidence: 99%
“…The results suggest that compounds isolated from E. cava have strong antiviral activity and may be developed into natural therapeutic drugs against SARS-CoV infection (Kwon et al 2013 ). A commercially available E. cava extract, Seapolynol™, was approved as a new dietary ingredient (NDI) by the US Food and Drug Administration in 2008 (FDA-1995-S-0039-0176) (Lee et al, 2012a , b ).…”
Section: Marine Algae and Spongesmentioning
confidence: 99%